The development and testing of the dementia friendly communities environment assessment tool (DFC EAT). (8th November 2016) - Fleming, Richard; Bennett, Kirsty; Preece, Terri; Phillipson, Lyn
ABSTRACT: Background: There is a growing recognition of the need to make the built environment in towns and cities more enabling for people with dementia. This study reports the development of a reliable tool to assess the support provided to people with dementia by public and commercial buildings such as council offices, supermarkets, banks, and medical centers as they approach, use, and leave them. Methods: A three-step process was carried out to develop and establish the reliability of the tool: (1) a review of principles and available tools informed the development and modification of an environmental audit tool of proven utility, (2) the draft tool was subjected to an iterative process of evaluation by a team of people with expertise in design and town planning, people with dementia and their carers, (3) inter-rater reliability and internal consistency were assessed on a sample of 60 public and commercial buildings. Results: The review of available tools led to the drafting of a tool that was refined through iterative, experience-based evaluation resulting in a tool that has high inter-rater reliability and internal validity. The data gathered enabled a sample of banks, libraries, shops, medical facilities, supermarkets and council offices to be compared. Conclusions: The new tool aids the collection of reliable information on the strengths and weaknesses of public and commercial buildings. This information is likely to be of use in the refurbishment of these buildings to improve their support of people with dementia as they use them in their daily life.